Elementos de inteligencia de negocio (BI) aplicada al análisis de datos en la Cooperativa de taxis "Benjamín Carrión" de la ciudad de Loja. - Vásquez Villalta, Karina Jhanova (2016)
This present job of titulation is aimed at the incorporation of business intelligence elements BI (Business intelligence) in the taxi cooperative "Benjamin Carrion" in the city of Loja. For proper implementation and integration a common data repository was required to perform not only extraction but processing and loading of information (EPL) from recognized data sources within the company. A Business Intelligence (BI) tool permits organization and analysis of data hosted in various different distinct databases in order to obtain knowledge to facilitate proper interpretation and understanding resulting in taking correct business decisions and thus giving a competitive advantage. Using user-oriented analysis tools it was possible to create xml schemas to map structures for OLAP processing in a standardized manner as well as layers of metadata required to achieve a good business model, i.e. improve the result of analysis regarding the relationships and the terminology of the physical database model. A business intelligence server was implemented to print schemes and metadata analysis and in this environment therefore the data is interpreted so that the platform user can view any information necessary by means of the online analytical processing tools (OLAP) In addition, supplemented with tools for generating reports and statistics, this business intelligence platform that integrates all of the above points, can support the information and analysis requirements vital to this establishment.